2017
DOI: 10.1016/j.aquaculture.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and physiological factors shape the gut microbiota of Atlantic salmon parr (Salmo salar L.)

Abstract: Gut microbes are key players in host immune system priming, protection and development, as well as providing nutrients to the host that would be otherwise unavailable. Due to this importance, studies investigating the link between host and microbe are being initiated in farmed fish. The establishment, maintenance and subsequent changes of the intestinal microbiota are central to define fish physiology and nutrition in the future. In fish, unlike mammals, acquiring intestinal microbes is believed to occur aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
292
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(328 citation statements)
references
References 54 publications
(110 reference statements)
30
292
5
1
Order By: Relevance
“…Since the focus of this study was not to evaluate individual protein sources, but the nutritional programming effect of first feeding diets, specific differences to other studies could also result from the used protein sources. The observed phyla in general were however quite consistent with previous results found for salmonids [51, 56, 64]. The core microbiome analysis performed in the present study demonstrated that fish fed either a fishmeal or a plant-protein based diet only share two OTUs after the first feeding period and none at the end of the second feeding period.…”
Section: Discussionsupporting
confidence: 92%
“…Since the focus of this study was not to evaluate individual protein sources, but the nutritional programming effect of first feeding diets, specific differences to other studies could also result from the used protein sources. The observed phyla in general were however quite consistent with previous results found for salmonids [51, 56, 64]. The core microbiome analysis performed in the present study demonstrated that fish fed either a fishmeal or a plant-protein based diet only share two OTUs after the first feeding period and none at the end of the second feeding period.…”
Section: Discussionsupporting
confidence: 92%
“…; Dehler et al . ). As a result, novel culture‐independent technologies have emerged as an opportunity to better understand this microbiota (Lan and Love ; Larsen et al .…”
Section: Pathogen Identification By Traditional Microbiologymentioning
confidence: 97%
“…Thus, the Illumina MiSeq platform approach is also useful in understanding and defining the intestinal microbiota of Atlantic salmon and has expanded previous studies performed by DGGE, TGGE and T‐RFPL (Dehler et al . ).…”
Section: Molecular Biology Identification Techniques and Their Applicmentioning
confidence: 97%
See 2 more Smart Citations